THE IMPORTANCE OF PREVENTION IN MEDICAL PRACTICE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pay special attention to prevention in reducing morbidity, mortality and disability. Preventive medicine is a complex of medical and social measures aimed at protecting and strengthening the health of the population, preventing the occurrence of diseases, and eliminating risk factors for their occurrence. Preventive medicine is named one of the priority areas of medical science, the formation and development of which is primarily determined by the systematization of concepts included in its subject and content. This article presents modern interpretations of the main definitions of preventive medicine.